1990
DOI: 10.1161/01.str.21.12.1663
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation-fibrinolysis abnormalities in acute and chronic phases of cerebral thrombosis and embolism.

Abstract: We assayed plasma concentrations of fibrinogen, fibrinopeptide A, plasmin-os plasmin inhibitor complex, D dimer, and antithrombin III activity in 40 patients with cerebral thrombosis and nine patients with cerebral embolism during the acute (<7 days), subacute (7-27 days), and chronic (>28 days) periods and compared these with 69 controls. In cerebral thrombosis, fibrinogen and fibrinopeptide A levels were elevated significantly in all stages (/7<0.001), whereas plasmin-a, plasmin inhibitor complex and D dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 44 publications
7
33
3
Order By: Relevance
“…D-dimer, which is a product of the degradation of cross-linked fibrin by plasmin, is the most frequently used indicator of activation of blood coagulation [24]. In agreement with previous suggestions [25], we recently reported that a high level of D-dimer after stroke is an independent predictor of cardioembolic aetiology [10].…”
supporting
confidence: 85%
“…D-dimer, which is a product of the degradation of cross-linked fibrin by plasmin, is the most frequently used indicator of activation of blood coagulation [24]. In agreement with previous suggestions [25], we recently reported that a high level of D-dimer after stroke is an independent predictor of cardioembolic aetiology [10].…”
supporting
confidence: 85%
“…Various studies have shown that the coagulation and fibrinolytic systems are activated in cerebral ischemia, and DD is the most frequently used indicator of blood coagulation activation. 23 After stroke, enhancement of the coagulation system reflects the mechanism of thrombus formation and vessel occlusion. In fact, thrombus formation in the cardiac chambers is mainly due to blood stasis, leading to a fibrinrich clot very similar to venous thrombi.…”
Section: Bnp and Dd For Cardioembolic Strokementioning
confidence: 99%
“…Therefore, these tests should generally be performed when the patient is not in an active thrombotic state and the coagulation and fibrinolytic factors have stabilized, usually 6 to 8 weeks after the thrombotic event. 3,4,15,16 Genetic tests such as the PCR for FVL and prothrombin gene mutation are not influenced by acute thrombosis.…”
Section: Coagulation Tests and Clinical Decision Making In Patients Wmentioning
confidence: 99%